dKDM5/LID regulates H3K4me3 dynamics at the transcription-start site (TSS) of actively transcribed developmental genes. - Lloret-Llinares, M.; Pérez-Lluch, S.; Rossell, D.; Morán, T.; Ponsa-Cobas, J.; Auer, H.; Corominas, M.; Azorín, F. (Nucleic Acids Research, 2012)
H3K4me3 is a histone modification that accumulates at the transcription-start site (TSS) of active genes and is known to be important for transcription activation. The way in which H3K4me3 is regulated at TSS and the actual molecular basis of its contribution to transcription remain largely unanswered. To address these questions, we have analyzed the contribution of dKDM5/LID, the main H3K4me3 demethylase in Drosophila, to the regulation of the pattern of H3K4me3. ChIP-seq results show that, at developmental genes, dKDM5/LID localizes at TSS and regulates H3K4me3. dKDM5/LID target genes are highly transcribed and enriched in active RNApol II and H3K36me3, suggesting a positive contribution to transcription. Expression-profiling show that, though weakly, dKDM5/LID target genes are significantly downregulated upon dKDM5/LID depletion. Furthermore, dKDM5/LID depletion results in decreased RNApol II occupancy, particularly by the promoter-proximal Pol llo(ser5) form. Our results also show that ASH2, an evolutionarily conserved factor that locates at TSS and is required for H3K4me3, binds and positively regulates dKDM5/LID target genes. However, dKDM5/LID and ASH2 do not bind simultaneously and recognize different chromatin states, enriched in H3K4me3 and not, respectively. These results indicate that, at developmental genes, dKDM5/LID and ASH2 coordinately regulate H3K4me3 at TSS and that this dynamic regulation contributes to transcription.